2017
DOI: 10.1371/journal.pone.0178730
|View full text |Cite
|
Sign up to set email alerts
|

Loose Panicle1 encoding a novel WRKY transcription factor, regulates panicle development, stem elongation, and seed size in foxtail millet [Setaria italica (L.) P. Beauv.]

Abstract: Panicle development is an important agronomic trait that aids in determining crop productivity. Foxtail millet and its wild ancestor green foxtail have recently been used as model systems to dissect gene functions. Here, we characterized a recessive mutant of foxtail millet, loose-panicle 1 (lp1), which showed pleiotropic phenotypes, such as a lax primary branching pattern, aberrant branch morphology, semi-dwarfism, and enlarged seed size. The loose panicle phenotype was attributed to increased panicle lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…In rice, overexpression of glucosamine (N‐acetyl)‐6‐sulfatase ( GNS 4) gene which codes for a cytochrome P450 caused increased panicle length and grain size, suggesting its role in regulating both panicle and grain characters (Zhou et al, ). The loose‐panicle 1 ( LP1 ) gene, which codes for WRKY transcription factor, was highly expressed in young inflorescence and seeds compared to other tissues of foxtail millet, indicating its involvement in regulating panicle development (Xiang et al, ). An overview of these results amply suggests that some of these genes are upregulated by the enhancer element in the activation‐tagged mutants of rice.…”
Section: Discussionmentioning
confidence: 99%
“…In rice, overexpression of glucosamine (N‐acetyl)‐6‐sulfatase ( GNS 4) gene which codes for a cytochrome P450 caused increased panicle length and grain size, suggesting its role in regulating both panicle and grain characters (Zhou et al, ). The loose‐panicle 1 ( LP1 ) gene, which codes for WRKY transcription factor, was highly expressed in young inflorescence and seeds compared to other tissues of foxtail millet, indicating its involvement in regulating panicle development (Xiang et al, ). An overview of these results amply suggests that some of these genes are upregulated by the enhancer element in the activation‐tagged mutants of rice.…”
Section: Discussionmentioning
confidence: 99%
“…The raw sequencing data was deposited at EMBL-EBI in the European Nucleotide Archive database under the accession number ERP106777 . Data from the two sample pools were aligned to each other and analyzed in accordance with methods described in our previous study ( Xiang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the use of bulked segregant analysis (BSA) to quickly analyze mutant collections generated by chemical mutagenesis ( Jiang et al, 2017 ) is accelerating Setaria gene discovery ( Xue et al, 2016 ; Fan et al, 2017 ; Huang et al, 2017 ). New genes contributing to leaf color ( Li et al, 2016 ), height, and inflorescence architecture ( Masumoto et al, 2016 ; Huang et al, 2017 ; Xiang et al, 2017 ; Yang et al, 2018 ) have been successfully identified with this approach, substantially advancing our understanding of important traits.…”
Section: Perspectives For Future Breedingmentioning
confidence: 99%